Strengthening Baduy Handicrafts Through Retail Management: A Case Study in Kanekes Village, Banten - T. Lisbet, Zeanette; Priyatna, Hilda Nanda; Shantilawati, Irma (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Baduy handicrafts, produced by the indigenous community in Kanekes Village, Banten, represent a unique blend of cultural heritage and sustainable craftsmanship. Despite their aesthetic and symbolic value, these products struggle to access wider markets due to limited digital literacy, informal marketing channels, and lack of export readiness. This study explores how retail management and digital adaptation strategies can enhance the competitiveness of Baduy crafts while respecting cultural norms.Using a participatory qualitative approach, the research involved interviews, observations, and group discussions with 25 Outer Baduy artisans on June 26-27, 2025. Findings reveal that artisans face challenges in pricing, product standardization, packaging, and platform usage (e.g., Amazon, Etsy). However, short-term interventions—such as branding, digital training, and basic e-commerce exposure—improved production quality, raised market awareness, and engaged youth as agents of innovation.The study concludes that culturally contextualized retail strategies can enable indigenous crafts to enter global markets without compromising identity. Strategic recommendations include capacity building in export logistics, platform onboarding, storytelling-based branding, and cooperative-based distribution systems. Empowering the younger generation and fostering collaboration are key to sustaining transformation. The Baduy case illustrates that tradition and technology can coexist to foster inclusive, ethical trade.